An optimised steelmaking-continuous casting scheduling simulation system with unity 3D. (7th May 2020) - Sun, Liangliang; Yu, Yaqian; Jin, Hang; Zhang, Li; An, Tingting
This work considers the transportation time involved in ladle allocation during the steelmaking-continuous casting production. The optimisation problem of equipment allocation is presented, the optimal production sequence is determined and a schedule for charges is determined. In order to ensure that the operation time and the energy consumption are minimised, a solution methodology combining heuristic algorithm and conflict elimination algorithm is developed. The simulation experiment based on actual production data shows that this methodology can effectively solve the steelmaking and continuous casting scheduling problem. To validate the scheduling plan more intuitively and modify it further, we present an optimisation system based on unity 3D simulation platform. The system can effectively evaluate the optimisation of the solution and adjust the related data to modify the scheduling plan and ultimately get a reasonable rescheduling plan.